The role of IL-2 in type 2 immunity - Tatsumi, Naoya; Kumamoto, Yosuke (Frontiers in Immunology, 2025)
Type 2 immune responses are essential for protective immunity against helminth parasites and for promoting tissue repair, but they can also drive allergic inflammation. T helper type 2 (Th2) cells and group 2 innate lymphoid cells (ILC2s) are key drivers of these responses, producing hallmark type 2 cytokines such as IL-4, IL-5, IL-9 and/or IL-13. While IL-2 has long been recognized as a T cell growth factor, emerging evidence reveals its central role in shaping Th2 cell fate and function. This review focuses on recent studies on how the availability of IL-2 is regulated in vivo for inducing Th2 cells. We also discuss the role of IL-2 in activating ILC2s and thereby linking innate and adaptive immune system in the context of type 2 immunity. Together, the studies discussed here highlight the role of IL-2 as a spatially and functionally dynamic coordinator of type 2 immunity.